Geospatial analysis of river flood hazard assessment - Soomro Riaz Ahmed; Nizamani Zafarullah; Nakayama Akihiko; Tan Kok Weng (E3S Web of Conferences, 2022)
Floods are one of the most damaging natural disasters which occur frequently in the world. They occur every year in Malaysia due to higher precipitation rates, river meandering, and heavily populated suburban areas. Monsoon rains are the major cause of floods and occur two times per year. The heavy floods in the Kelantan River Basin have shown an increasing trend in recent years. Terrain characteristics of the land and meteorological properties of the region are the main natural factors for this disaster. In this study, the Kuala Krai district of the Kelantan River is selected to be reviewed as the case study for flood risk analysis. Geographical Information System (GIS) integrated with Multicriteria Decision Analysis (MCDA) can be used to evaluate the potential flood risk areas. Historically flooded areas can be extracted from the satellite images to determine flood causing factors for the analysis. At the end of the study, a map of flood risk areas can be generated and validated to assist decisionmakers on the menace posed by the disaster. The expected results obtained from the study will help the guidance city planners and administrators to choose safe sites for construction and development. This study will also help to provide flood mitigation and quick relief response for the red zone areas which are more likely to hit badly from flood hazards. The study will help the Malaysian government to reduce natural flood risks in Malaysia which are one of the top causes of damage.